Pengejawantahan EU GDPR dalam RUU Perlindungan Data Pribadi: Penguatan Perlindungan Data Pemilih oleh KPU - Laila Alfina Mayasari Rizqi; Syahrico Radya Fahrezi; Tjokorda Istri Diah Candra Permatasari (Faculty of Law, Universitas Airlangga, 2022)
AbstractThe case of leaking permanent voter data for the 2014 general election (Pemilu) emerged in May 2020. The vulnerability of personal data breaches is the raison d'etre of the legal umbrella that specifically regulates the protection of personal data. On the other hand, the government continues to improve the Personal Data Protection Bill (PDP). One of the substances of concern is the imbalance between the rights of the data owner and the responsibility of the data controller. This article answers the problem regarding the urgency of the ratification of the PDP Bill so that it can serve as a guide for the KPU as the election organizer who is responsible for the protection of voter data through the embodiment of the EU GDPR. Through a normative juridical research method with a statutory approach, case approach, and comparative approach, this research produces a solution to strengthen the responsibility of the KPU and at the same time encourage the ratification of the PDP Bill in Indonesia.Keywords: KPU; Voter Data; PDP Bill; EU GDPR.AbstrakKasus bocornya data pemilih tetap pemilihan umum (Pemilu) 2014 mencuat pada Mei 2020 lalu. Rentannya pelanggaran data pribadi tersebut menjadi raison d’etre payung hukum yang secara khusus mengatur perlindungan data pribadi. Di sisi lain, pemerintah terus berupaya menyempurnakan Rancangan Undang-Undang Perlindungan Data Pribadi (PDP). Salah satu substansi yang menjadi perhatian yaitu timpangnya hak pemilik data dengan tanggung jawab pengendali data. Artikel ini menjawab permasalahan mengenai urgensi pengesahan RUU PDP sehingga dapat menjadi pedoman KPU sebagai penyelenggara Pemilu yang bertanggung jawab atas perlindungan data pemilih melalui pengejawantahan EU GDPR. Melalui metode penelitian yuridis normatif dengan pendekatan perundang-undangan, pendekatan kasus, dan pendekatan komparatif. Penelitian ini menghasilkan gagasan solutif untuk memperkuat tanggung jawab KPU serta sekaligus mendorong pengesahan RUU PDP di Indonesia.Kata Kunci: KPU; Data Pemilih; RUU PDP; EU GDPR.